INTEGRASI TEORI PELAKU DAN RISIKO UNTUK MEMBANGUN KERANGKA KEPATUHAN PAJAK DI INDONESIA - Zahra Yusuf, Nasywa Nurunnabilah; ahmad, saidah; Sakinah, Gina (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2025)
Tax compliance in Indonesia continues to face significant challenges, particularly in the aspect of voluntary compliance. This article aims to develop an integrative conceptual framework by combining the Theory of Planned Behavior (TPB) and tax risk management to enhance the effectiveness of tax compliance policies. The method employed is a systematic literature review based on the PRISMA approach, focusing on articles indexed. The synthesis reveals that psychological factors such as attitude, subjective norms, and perceived behavioral control are closely intertwined with risk perception, which is managed through Compliance Risk Management (CRM) strategies. The integrative framework positions risk perception as a mediating variable linking tax compliance intention and actual behavior, while also reinforcing CRM’s moderating function. These findings offer theoretical contributions by bridging psychological and managerial approaches, as well as practical implications for designing tax policies that are data-driven and aligned with taxpayer behavior.